2020
DOI: 10.3389/fpsyg.2020.00843
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Changes in the Orbitofrontal-Paralimbic Cortex in Male Youths With Non-comorbid Conduct Disorder

Abstract: Conduct disorder is one of the most common developmental psychiatric disorders which is characterized by persistent aggressive and antisocial behaviors during childhood or adolescence. Previous neuroimaging studies have investigated the neural correlates underlying CD and demonstrated several constructive findings. However, Individuals with CD are at high risk for comorbidities, which might give rise to the inconsistencies of existed findings. It remains unclear which neuroanatomical abnormalities are specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 103 publications
(142 reference statements)
1
5
0
Order By: Relevance
“…CD may accompany many psycho-developmental issues such as substance abuse, depression, anger problems, and in some instances, the lack of empathy, which is the hallmark of callous-unemotional (CU) traits. CD is also a major risk factor for developing antisocial personality disorder (ASPD) 2 , 4 . The behavioral hallmarks of the ASPD are the same as CD, and it also follows the same gender difference: it is more prevalent in males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD may accompany many psycho-developmental issues such as substance abuse, depression, anger problems, and in some instances, the lack of empathy, which is the hallmark of callous-unemotional (CU) traits. CD is also a major risk factor for developing antisocial personality disorder (ASPD) 2 , 4 . The behavioral hallmarks of the ASPD are the same as CD, and it also follows the same gender difference: it is more prevalent in males.…”
Section: Introductionmentioning
confidence: 99%
“…Structural MRI studies also supported a lack of social cognition and emotion in CD subjects. There is evidence of decreased gray matter in various parts of the brain associated with such responses, including lower volumes of the left amygdala, right insula, left medial superior frontal gyrus, and left fusiform gyrus in CD patients 4 , 12 . On the other hand, some studies observed increased gray matter of the orbitofrontal cortex while others reported reduced volume comparing CD adults with healthy subjects 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, structural magnetic resonance imaging (sMRI) has been used to investigate the anatomical brain changes underlying CD, reflected by various morphometry parameters, including grey matter volume (GMV; i.e., cortical and subcortical volume [CV/SCV]). While a clear and consistent picture of the structural brain alterations seen in patients with CD remains lacking, two meta-analyses (each based on over 10 studies) of youth with CD, oppositional defiant disorder (ODD), or conduct problems concluded these conditions were associated with reductions in volume in cortical (ventrolateral, medial prefrontal, middle temporal, superior temporal, and anterior insular cortices) and subcortical (amygdala, caudate and putamen) regions [ 11 12 ] though it should be noted that there have been several reports of both increased GMV in participants with CD relative to the controls in many of these regions since these meta-analyses were published [ 13 15 ] and a lack of group differences in GMV [ 16 19 ]. Within the pathology of CD, recent longitudinal studies suggested that higher CD-related symptomatology was associated with accelerated age-related cortical thinning [ 20 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD may accompany many psycho-developmental issues such as substance abuse, depression, anger problems, and lack of empathy, which is the hallmark for callous-unemotional (CU) traits. It is also a major risk factor for developing antisocial personality disorder (ASPD) [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Structural MRI studies also supported a lack of social cognition and emotion in CD subjects. There is evidence of decreased gray matter in various parts of the brain associated with such responses, including lower volumes of left amygdala, right insula, left medial superior frontal gyrus, and left fusiform gyrus in CD patients [3, 6]. On the other hand, some studies observed increased gray matter of the orbitofrontal cortex while the others reported reduced volume comparing CD adults with healthy subjects [7, 8].…”
Section: Introductionmentioning
confidence: 99%